Caffeine intake and the risk of chronic obstructive pulmonary disease in Japanese adults - Hirayama, Fumi; Lee, Andy; Yasukawa, K.; Ishihara, Y.; Shinjo, M. (Mary Ann Liebert, Inc. Publishers, 2012)
Background: To investigate the association between caffeine intake and the risk of developing chronic obstructive pulmonary disease (COPD) among Japanese older adults, a case–control study was conducted in central Japan. Methods: A total of 277 patients with COPD aged 50 to 75 years were referred by respiratory physicians, while 340 controls were recruited from the community. All participants had their disease status confirmed by spirometry. Information on habitual caffeine intake, demographic, and lifestyle characteristics was obtained by face-to-face interview using a validated questionnaire. Results: The COPD patients drank more coffee and had a higher mean caffeine intake (311.3, SD 176.2mg/day) than the control group (278.4, SD 188.1 mg/day), p = 0.03. Relative to nondrinkers, the risk of COPD apparently increased for those drinking at least two cups of coffee daily (adjusted odds ratio 1.58, 95% confidence interval [CI] 0.93 to 2.71). Similarly, total caffeine intake was associated with the prevalence of COPD—the adjusted odds ratio being 1.30 (95% CI 1.09 to 2.12) for consuming over 312mg/day when compared to a low intake of less than 184mg/day. Conclusions: The epidemiological evidence suggested a positive association between caffeine intake and the development of COPD in Japanese adults. Further study of the effect of caffeine on lung function and the risk of COPD should be undertaken.